Proteostasis unbalance in prion diseases: Mechanisms of neurodegeneration and therapeutic targets - Thellung, Stefano; Corsaro, Alessandro; Dellacasagrande, Irene; Nizzari, Mario; Zambito, Martina; Florio, Tullio (Frontiers in Neuroscience, 2022)
Transmissible spongiform encephalopathies (TSEs), or prion diseases, are progressive neurodegenerative disorders of central nervous system that affect humans and animals with sporadic, inherited and infectious forms. Similarly, to Alzheimer disease and other neurodegenerative disorders, any attempt to reduce TSE lethality or at least increase life expectancy of affected individuals was unsuccessful. Typically, the onset of symptoms anticipates the fatal outcome of less than one year, although it is believed to be the consequence of decades-long process of neuronal death. The duration of symptoms-free period represents by itself a major obstacle to carry our effective neuroprotective therapies. TSEs recognize, as unifying pathogenic event the post-translational refolding of the glycoprotein cellular prion protein (PrPC) which is highly expressed in the brain, into an amyloidogenic conformer named prion protein scrapie (PrPSc) from the ovine prototypical TSE. PrPSc is resistant to intracellular turnover and undergoes to amyloid-like fibril aggregation passing through the formation of soluble dimers and oligomers, which are likely the effective neurotoxic entities. The failure of PrPSc elimination through proteostatic mechanisms is a TSE key pathogenic event shared by other neurodegenerative disorders, including Alzheimer and Parkinson diseases, which allows their classification as proteopathies. Under physiological conditions, protein quality control, led by ubiquitin-proteasome system, and macroautophagy cooperate to clear cytoplasm from improperly folded, redundant, or aggregation-prone proteins. There is evidence that both of these crucial homeostatic pathways are impaired during the development of TSEs although is still unclear if proteostasis alteration facilitates prion protein misfolding or, rather, PrPSc protease resistance hampers cytoplasmic protein quality control. This review is aimed to critically analyze the most recent advancements about cause-effect correlation between PrPC misfolding and proteostasis alterations, and to discuss the possibility that pharmacological restoring of ubiquitin-proteosomal competence and stimulation of autophagy could reduce intracellular burden of PrPSc and ameliorate severity of prion-associated neurodegeneration.